Theorising the Avant-Garde : Modernism, Expressionism, and the Problem of Postmodernity. - Murphy, Richard (Richard John) (Literature, culture, theory., 1999)
Richard Murphy mobilises theories of the postmodern to challenge our understanding of the avant-garde and assesses its importance for the debates among theorists of postmodernism such as Jameson, Eagleton, Lyotard and Habermas. Combining film and literature, this project will appeal to all those interested in twentieth-century modernist movements and postmodernity.